Profit maximizing goes global: The race to the bottom - David Kiefer; Codrina Rada (The University of Utah, Department of Economics, 2013)
We explore four decades of cyclical and long-run dynamics in income distribution and economic activity for a panel of thirteen OECD countries, as measured by the wage share and the output gap. When modeled as a Goodwin model, our results suggest that economic activity is weakly profit-led and that the wage share is pro-cyclical. Our estimated model is dynamically stable and has a long-run equilibrium in distributionutilization space. An extension of the model suggests that this equilibrium has been shifting south-west towards a lower wage share and a loss of economic activity. This finding is suggestive of a coordination failure among industrialized nations; it could be that the governments of these countries are engaging in a race to the bottom in terms of the wage share; it may even be that this race has the undesirable consequence of decreasing economic efficiency.
Keywords: D3; C23; C61; 330; predator-prey models; distributive-demand dynamics; panel data estimation